2012
DOI: 10.1111/all.12062
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of the bronchial tree from beginning to end: targeting small airway inflammation in asthma

Abstract: To cite this article: van den Berge M, ten Hacken NHT, van der Wiel E, Postma DS. Treatment of the bronchial tree from beginning to end: targeting small airway inflammation in asthma. Allergy 2013; 68: 16-26.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 80 publications
1
51
0
2
Order By: Relevance
“…Thus, surfactant is an interesting source of potential biomarkers. Currently, there is large interest in understanding the involvement of the distal airways in the development and progression of respiratory diseases, such as asthma and chronic obstructive pulmonary disease (COPD) (14,15 ). For a long time the distal airways were not accessible and therefore were often referred to as the "silent zone" of the lungs.…”
Section: Surfactantmentioning
confidence: 99%
“…Thus, surfactant is an interesting source of potential biomarkers. Currently, there is large interest in understanding the involvement of the distal airways in the development and progression of respiratory diseases, such as asthma and chronic obstructive pulmonary disease (COPD) (14,15 ). For a long time the distal airways were not accessible and therefore were often referred to as the "silent zone" of the lungs.…”
Section: Surfactantmentioning
confidence: 99%
“…[13] An advantage of small-particle instead of large-particle inhaled treatment could be a higher total lung deposition in addition to better deposition in the small airways. [4,5] Yet, we are currently not able to select asthma patients with small airway dysfunction, i.e. those who will probably benefit most from the inhaled small-particle medication.…”
Section: Introductionmentioning
confidence: 99%
“…A number of clinical studies have shown that small particle ICS therapies, with aerosol MMAD values of approximately 1 μm, reduce airway hyperresponsiveness and improve asthma symptoms as well as quality of life (5, 7, 12). The small particle ICS products are expected to improve drug mass delivery to the small airways, which is consistent with multiple in vivo (7579) and recent complete-airway CFD predictions (80, 81).…”
Section: Discussionmentioning
confidence: 99%
“…The small airways can be classified as having an internal diameter < 2 mm, do not contain cartilage, and generally start with the 8th airway generation together with the alveolar region (7, 12). The small tracheobronchial (TB) airways can be considered to start at approximately bifurcation B8 and continue through the terminal bronchioles at approximately B15, which then lead to the alveolar airways (13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation